2006
DOI: 10.1007/s11250-006-4231-9
|View full text |Cite
|
Sign up to set email alerts
|

Examination of non-genetic factors affecting the growth performance of djallonke sheep in soudanian zone at the Okpara breeding farm of Benin

Abstract: A study was carried out at the Okpara breeding farm in Benin. Records on 558 lambs of the Djallonke sheep breed, born from 1997 to 2000, were used to determine the weekly growth curve from birth up to 119 days of age. Non-genetic factors affecting lamb weights at birth and at 30, 60, 90 and 120 days and average daily gains from 0 to 30 days, from 0 to 60 days, from 0 to 90 days and from 0 to 120 days were investigated. A linear model comprising the fixed effects of birth season, birth year, parity number of ew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
6
11
0
1
Order By: Relevance
“…High values of the parameter k indicate that the animals reach maturity earlier (Brown et al, 1976;Carolino and Gama, 1993;McManus et al, 2003), and, as can be observed in Table 3, females have a higher rate of maturity (between 0.005 and 0.028) than males (between 0.003 and 0.027), as was also observed by Bathaei and Leroy (1998), Gbangboche et al (2008), Ulutas et al (2010), and, consequently, have a lower weight at maturity. The growth rates estimated by these models showed that females grow at a higher rate than males, although the differences between males and females were quite small, and always in favour of females, as reported in previous studies (Bathaei and Leroy, 1998;Gbangboche et al, 2006;Ulutas et al, 2010). The Brody model estimated the lowest growth rates for males and females, whereas the Verhulst model estimated the highest growth rates in both sexes.…”
Section: Resultssupporting
confidence: 81%
“…High values of the parameter k indicate that the animals reach maturity earlier (Brown et al, 1976;Carolino and Gama, 1993;McManus et al, 2003), and, as can be observed in Table 3, females have a higher rate of maturity (between 0.005 and 0.028) than males (between 0.003 and 0.027), as was also observed by Bathaei and Leroy (1998), Gbangboche et al (2008), Ulutas et al (2010), and, consequently, have a lower weight at maturity. The growth rates estimated by these models showed that females grow at a higher rate than males, although the differences between males and females were quite small, and always in favour of females, as reported in previous studies (Bathaei and Leroy, 1998;Gbangboche et al, 2006;Ulutas et al, 2010). The Brody model estimated the lowest growth rates for males and females, whereas the Verhulst model estimated the highest growth rates in both sexes.…”
Section: Resultssupporting
confidence: 81%
“…Indeed, the first-parity ewes are still growing, implying the competition for nutrient with the foetuses (London and Weniger, 1995). The incidence of year ( Figure 3b) was reported in previous studies (Ebangi et al, 1996and Gbangboche et al, 2006aand 2006b) and could be due to the changes during the year, in management, herdsman's skills and other environmental factors.…”
Section: Model Parameterssupporting
confidence: 54%
“…The shape of the growth curve showed that male ( Figure 2a) and single lambs ( Figure 2b) were heavier than female and twin lambs, respectively. The higher weight of male than female has been described in WAD sheep (London and Weniger, 1995;Ebangi et al, 1996;Gbangboche et al, 2006b) and could be attributed to the hormonal and physiological differences between sexes (Ebangi et al, 1996). The superiority of single lambs over Selected model: A is the predicted asymptotic weight at maturity (kg), B is the proportional difference between A and birth weight (kg) and k is the rate of maturating.…”
Section: Model Parametersmentioning
confidence: 93%
See 1 more Smart Citation
“…Several different growth models have been used to describe the growth pattern and development of body weight in pigs (Knap, 2000;Wellock, 2004;Koivula et al, 2008), cattle (Brown et al, 1976;Beltran et al, 1992;Berry et al, 2005), and sheep (Lewis et al, 2002;Gbangboche et al, 2006;Gbangboche et al, 2008). Fixed (Afolayan et al, 2006) and random polynomial regression (Meyer, 2005) Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/livsci have also been used.…”
Section: Introductionmentioning
confidence: 99%